PENGARUH PROMOSI DAN KUALITAS PELAYANANTERHADAP MINAT BELI KONSUMEN PADA ECLAIRESHOP DI CIPONDOH TANGERANG - Aisyah Nur Cahya; Abdul Khoir (Yayasan Sahabat Cendekia Jaya, 2024)
This research aims to determine the influence of promotions and service quality on buying interest in Eclaire Shop Cipondoh. The population in this study was 29,600 people. The sample selection in this research was 100 people using the Slovin technique. The analytical method used in this research is descriptive statistical analysis, quantitative analysis. The results of this research show that the promotional variable has a significant effect on purchasing interest at Eclaire Shop Cipondoh with a regression value of 0.731. The T-count < T-table value is 2.798 > 1.66088. The service quality variable has a significant effect on purchasing interest at Eclaire Shop Cipondoh with a regression value of 0.699. The T-count > T-table value is 7.046 > 1.66088. Promotion variables and service quality simultaneously and significantly influence purchasing interest at Eclaire Shop Cipondoh. So the value of F-count > F-table is 2.798 > 1.66088. The sig value of the F test is 0.000 < 0.05